PENGARUH GOOD CORPORATE GOVERNANCE PADA KINERJA BERBASIS BALANCED SCORECARD - Pratiwi, Ni Luh Putu Andriyani; Putri, I Gusti Ayu Made Asri Dwija (E-Jurnal Akuntansi, 2016)
Good corporate governance (GCG) is a corporate governance system that serves as a means of control to regulate the structure and mechanism of the company. Corporate governance practices can enhance corporate value by improving performance from a financial perspective, customer perspective, internal business processes, and learning and growth perspective. This research aims to determine the effect of corporate governance on the performance-based balanced scorecard in rural banks (BPR) in Denpasar city and Badung regency. GCG principles used is transparency, accountability, responsibility, independency, and fairness. The samples were 65 rural banks in Denpasar city and Badung regency. The data used are primary data using a questionnaire instrument. Analysis using multiple regression analysis techniques. Based on this research, the principles of good corporate governance affects the performance-based balanced scorecard in rural banks.
Keywords: good corporate governance, transparency, accountability, responsibility, independency, fairness, performance, balanced scorecard